Weather proverbs - Dunwoody, H. H. C. (Henry Harrison Chase), 1842-1933 (Salt Lake City, UT : Project Gutenberg, 2024)
"Weather Proverbs" by H. H. C. Dunwoody is a scientific compilation likely written in the late 19th century. The work serves as a collection of popular weather proverbs and prognostics, focusing on the traditional wisdom surrounding weather prediction drawn from nature, particularly the behaviors of animals, plants, and atmospheric conditions. Through this exploration, the book seeks to bridge the gap between folklore and modern meteorological observations, making it a fascinating read for those interested in weather lore and its applications. The opening of the publication introduces the scope and intention behind the collection, highlighting the collaboration between meteorologists and the general public to gather weather-related sayings. Dunwoody explains that many of these proverbs express observable patterns in the behavior of animals and environmental changes that can precede specific weather phenomena. He emphasizes that while these proverbs encapsulate a form of traditional knowledge$1 (Boften based on keen observations made by farmers, sailors, and others close to nature$1 (Bthey are not substitutes for modern meteorological science, which relies on systematic measurements and observations. The introduction sets the stage for an extensive collection of proverbs that underscore long-standing human attempts to understand and predict weather changes. (This is an automatically generated summary.)s
Release date is 2024-12-16
Richard Tonsing and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Weather -- Folklore